The Multiplicity of Voices in the Novel Noir Al-Almond - the Alienation of Saleh bin Amer Alzofari by Wasseni AlAraj - قشي محمد (Milev Journal of Research and Studies, 2023)
The Democracy of Narrative Unfolds Through the Multiplicity of Characters' Voices, and the Freedom They Find in Expressing Their Opinions, Allowing for the Revelation of the Text's Hidden Layers and Presentation to the Reader. "Nawar Al-Lawz" Novel by Wasen Al-Araj as a Case Study for This Type of Novels. In this article, we attempted to extract the surface and underlying dimensions and meanings, as well as the multiplicity of voices and how they manifest within the Algerian novel in general and the novel "Nawar Al-Lawz" in particular. The title of the article is "The Multiplicity of Voices in the Novel Nawar Al-Lawz: A Study of the Novel's Democracy by Saleh bin Amer Al-Zaufari and Wasen Al-Araj." The research aims to extract the multiplicity of voices and demonstrate their democracy within the Algerian narrative text in general and the novel "Nawar Al-Lawz" in particular. These voices include the voice of the people, the voice of injustice, and the voice of the oppressed.